Regulation of Labor with Disabilities in Facing the Digital Revolution: Comparison of Indonesia, Malaysia and Australia - Vicko Taniady; Reni Putri Anggraini; Novi Wahyu Riwayanti (Journal of Judicial Review, 2021)
This study focuses on research on persons with disabilities in the employment sector. The research method used is normative law by using library research techniques to process secondary data and a comparative study approach. The results of this study reveal that Article 27 paragraph (2) of the 1945 Constitution of the Republic of Indonesia guarantees that every citizen has the right to have the same rights in work. In addition, several policies such as Law no. 8 of 2016 and Law no. 12 of 2003 have regulated the same thing to eliminate discrimination in the workforce. However, the existing policies are still not running according to the applicable regulations. People with disabilities in Indonesia still experience discrimination in getting a job, so the unemployment rate for people with disabilities is still high. In addition, with the entry of the industrial revolution 4.0 era in Indonesia, it is increasingly difficult for people with disabilities to find work. Thus, there is a need for regulatory reformulation to become the right of persons with disabilities in employment based on the policies of Malaysia and Australia.